Perbandingan Performa Tools Web Scraping pada Website dengan Data Statis dan Dinamis - Michael Levi; Henry Novianus Palit; Silvia Rostianingsih (Jurnal Infra, 2020)
In scraping a website, the main concern is the type of website whether it is a static or dynamic website, and also the data structure of the website. With different website characteristics and diverse web scraping tools, it will make users quite difficult in choosing tools that suit their needs. The purpose of this research is to compare web scraping tools from different website characteristics, and to provide recommendations for web scraping tools for future research by knowing the right tools in handling each website's characteristics. Based on the results of tests that have been done, it can be concluded which tools are more effective and efficient in certain conditions.